2018
DOI: 10.7150/ijbs.28288
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived from Hypoxic Colorectal Cancer Cells Transfer Wnt4 to Normoxic Cells to Elicit a Prometastatic Phenotype

Abstract: Hypoxia is the most common characteristic of solid tumours driving cancer metastasis. Cancer cells release exosomes with various functions into the tumour microenvironment during cancer progression. However, the roles and associated mechanisms of hypoxic colorectal cancer (CRC) cell-derived exosomes remain poorly understood. Here, we found that exosomes secreted by hypoxic CRC cells promoted the migration and invasion abilities of normoxic CRC cells. Inhibition of exosome secretion by GW4869 reduced hypoxic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 38 publications
(38 reference statements)
1
65
0
Order By: Relevance
“…Since CAFs conditioned media attracted more migrated cancer cells, there might be cytokines, chemokines or other factors contributing to invasion and metastasis of GC cells. Exosome can be taken up by neighboring or distant cells, subsequently leading to changes in gene expression, and it plays a crucial role in cancer biology with vesicular transport [21][22][23][24][25][26]. In our study, exosomal MMP11 was found overexpressed in gastric CAFs.…”
Section: Discussionsupporting
confidence: 49%
“…Since CAFs conditioned media attracted more migrated cancer cells, there might be cytokines, chemokines or other factors contributing to invasion and metastasis of GC cells. Exosome can be taken up by neighboring or distant cells, subsequently leading to changes in gene expression, and it plays a crucial role in cancer biology with vesicular transport [21][22][23][24][25][26]. In our study, exosomal MMP11 was found overexpressed in gastric CAFs.…”
Section: Discussionsupporting
confidence: 49%
“…Different groups have investigated the role hypoxia could have in exosome transfer and the induction of change upon uptake by other cells. Work in hypoxic breast [59], lung [60], and colorectal [61] cancer-derived exosomes has identified different miRNAs to play a role in angiogenesis. Exosomes from hypoxic BC cells released miR-201 once taken up by TME cells, inducing increased expression of genes involved in the vasculature remodelling, as well as an increased proliferation, migration, and induction of capillary-like structures in vitro compared to cells not exposed to exosomes [59].…”
Section: Neo-angiogenesismentioning
confidence: 99%
“…To confirm the role of this miR-23a in the angiogenic process, the inhibition of miR-23a in mice models reduced growth and angiogenesis in vivo [60]. Exosomes from hypoxic CRC cells induced migration and invasion when taken up by CRC under normoxic conditions via the Wnt4-HIF1α signalling cascade [61].…”
Section: Neo-angiogenesismentioning
confidence: 99%
“…Chen et al 33 performed omics profiling and reported that transcriptional and translational downregulations of human colon cancer-associated genes activated exosomes as well as proteinic factors modifications in endoplasmic reticulum (ER), which was relevant to a higher risk of malignant metastatic behaviors. And Huang et al 34 proposed that hypoxic CRC cells promoted Wnt4-carried exosomes to achieve β-catenin translocation into the nucleus in adjacent normal tissue, which further drove CRC metastasis (Table 1). Thus, hypoxic microenvironment is a potent factor in augmenting metastasis and it remains a major therapeutic challenge in clinic, however.…”
Section: Cancer Metastasismentioning
confidence: 99%